On Hölder continuity of solutions of doubly nonlinear parabolic equations with weight - Bonafede, S.; Skrypnik, I.I. (Український математичний журнал, 1999)
We prove the Hölder regularity of bounded weak solutions of doubly nonlinear degenerate parabolic equations with measurable coefficients. Доведено регулярність за Гельдером обмежених слабких розв'язків вироджених параболічних рівнянь з подвійною неліниійністю та вимірними коефіцієнтами.